Molecular profiling of soft-tissue sarcomas with FoundationOne® Heme identifies potential targets for sarcoma therapy: a single-centre experience. (July 2021) - Scheipl, Susanne; Brcic, Iva; Moser, Tina; Fischerauer, Stefan; Riedl, Jakob; Bergovec, Marko; Smolle, Maria; Posch, Florian; Gerger, Armin; Pichler, Martin; Stoeger, Herbert; Leithner, Andreas; et al.
Background: Molecular diagnosis has become an established tool in the characterisation of adult soft-tissue sarcomas (STS). FoundationOne ® Heme analyses somatic gene alterations in sarcomas via DNA and RNA-hotspot sequencing of tumour-associated genes. Methods: We evaluated FoundationOne ® Heme testing in 81 localised STS including 35 translocation-associated and 46 complex-karyotyped cases from a single institution. Results: Although FoundationOne ® Heme achieved broad patient coverage and identified at least five genetic alterations in each sample, the sensitivity for fusion detection was rather low, at 42.4%. Nevertheless, potential targets for STS treatment were detected using the FoundationOne ® Heme assay: complex-karyotyped sarcomas frequently displayed copy-number alterations of common tumour-suppressor genes, particularly deletions in TP53, NF1, ATRX, and CDKN2A . A subset of myxofibrosarcomas (MFS) was amplified for HGF ( n  = 3) and MET ( n  = 1). PIK3CA was mutated in 7/15 cases of myxoid liposarcoma (MLS; 46.7%). Epigenetic regulators (e.g. MLL2 and MLL3 ) were frequently mutated. Conclusions: In summary, FoundationOne ® Heme detected a broad range of genetic alterations and potential therapeutic targets in STS (e.g. HGF/MET in a subset of MFS, or PIK3CA in MLS). The assay's sensitivity for fusion detection was low in our sample and needs to be re-evaluated in a larger cohort.